“Something very taboo”: a qualitative exploration of beliefs, barriers, and recommendations for improving mental health care and access for Hispanic adults in the Paso del Norte U.S.-Mexico border region - Mallonee, Jason; Escalante, Rosa; Robles, Eden Hernandez; Tucker, Christal (Frontiers in Public Health, 2023)
Background Hispanic adults with mental health conditions in the United States experience disproportionate access to and utilization of professional mental health treatment. This is believed to be in part due to systemic barriers and challenges, difficulty accessing care, cultural factors, and stigma. Studies to date have failed to examine these specific factors within the unique context of the Paso del Norte U.S.-Mexico border region. Methods For this study, 25 Hispanic adults identifying primarily of Mexican descent participated in four focus groups exploring these topics. Three groups were facilitated in Spanish and one group in both English and Spanish. Focus groups followed a semi-structured format eliciting perspectives on mental health and mental illness, help-seeking, barriers and facilitators of help-seeking and treatment access, and recommendations for mental health agencies and providers. Results Qualitative data analysis yielded the following themes: understanding of mental health and help-seeking; barriers to accessing care; mental health treatment facilitators; and recommendations for agencies, providers, and researchers. Conclusion Findings from this study support the need for innovative mental health engagement strategies to reduce stigma, increase understanding of mental health, foster support systems, reduce individual and systemic barriers to seeking and accessing care, and to continue to engage communities in mental health outreach and research.